360-degree video Virtual Reality : One Day Trip in Kuala Lumpur - Ab Ghani, Zuriani (Journal of Computing Technologies and Creative Content, 2019)
Virtual reality (VR) offers powerful new ways to experience and explore stories. Bringing the experience of the environment and the ambience of the attraction spot among tourists in 360degree video Virtual Reality (VR). Providing information about the attraction spot to the tourists via virtually interacting with the interface. In Malaysia, there is still an apparent lack of 360degree Virtual Reality (VR) application as a medium. The application will work around using interactive Virtual Reality (VR) interface in 360-degree view. The aim is to make the tourists feel as if they are really at that place, even though they may actually be on the real life.